Interior Revitalization of Indonesian National Building Gresik with Art Deco Themed Damar Kurung - Dhimastahta Dhanar Gumilang; Sumarno Sumarno; Harmilyanti Sulistiyani (Institut Seni Indonesia Surakarta, 2021)
The Interior Revitalization Planning at the Indonesia National Building in Gresik by adapting Art Deco Style with the theme